2018
DOI: 10.1002/humu.23389
|View full text |Cite
|
Sign up to set email alerts
|

Cisvariants identified in F508del complex alleles modulate CFTR channel rescue by small molecules

Abstract: Molecules correcting the trafficking (correctors) and gating defects (potentiators) of the cystic fibrosis causing mutation c.1521_1523delCTT (p.Phe508del) begin to be a useful treatment for CF patients bearing p.Phe508del. This mutation has been identified in different genetic contexts, alone or in combination with variants in cis. Until now, 21 exonic variants in cis of p.Phe508del have been identified, albeit at a low frequency. The aim of this study was to evaluate their impact on the efficacy of CFTR-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 35 publications
5
37
0
3
Order By: Relevance
“…For secondary mutations which induced CFTR misfolding (M152W, M156W, H199W/A and I368W), both F508del and L206W correction was prevented (Fig. S3 (D and E)), in this case probably due to additive folding defects, as was previously demonstrated for cis mutation L467F (25). Of note, cis-mutations F87L and L53V which prevented VX-809 correction of F508del CFTR are located in the vicinity of the inner binding site (Fig.…”
Section: Exploring Key Residues Of the Msd1 Vx-809 Binding Pocketssupporting
confidence: 65%
See 1 more Smart Citation
“…For secondary mutations which induced CFTR misfolding (M152W, M156W, H199W/A and I368W), both F508del and L206W correction was prevented (Fig. S3 (D and E)), in this case probably due to additive folding defects, as was previously demonstrated for cis mutation L467F (25). Of note, cis-mutations F87L and L53V which prevented VX-809 correction of F508del CFTR are located in the vicinity of the inner binding site (Fig.…”
Section: Exploring Key Residues Of the Msd1 Vx-809 Binding Pocketssupporting
confidence: 65%
“…We have previously shown that cis mutations of F508del could alter the response to VX-809 treatment, either by inducing an additional folding defect as for L467F (25) or by altering a potential VX-809 binding site as suggested with F87L (26). Here, we evaluated the effect of L53V, another cis mutation located in the N-terminal part of CFTR, called the lasso motif and defined after the first high-resolution experimental 3D structures of zebrafish and human CFTR (27,28).…”
Section: A Potential Vx-809 Binding Site Highlighted Within Msd1 By Molecular Dockingmentioning
confidence: 99%
“…Moreover, the effects of Lumacaftor were neither global nor of equal efficacy for all Class II variants [99], similar to what is seen with Vx770 in the potentiation of class III CF variants. Its use in combination with Vx770, referred to as Orkambi [93, 100103], to potentiate the channel gating of the cell surface delivered F508del variant, was approved by the FDA for use in patients carrying at least one F508del variant allele in 2015. Taken together, these data highlight the need for a better understanding of the mechanism of action of therapeutics to predict the spectrum of variants for which Lumacaftor and Orkambi will be efficacious for personalized medicine-based approach for ER-restricted class II variants.…”
Section: Resultsmentioning
confidence: 99%
“…The variant L467F, found in cis with F508del in patient two, is a rare variant (exact frequency 0.00005%) first identified in France (and reported in CF Mutation Database). It was identified in one case out of 56 in a study of children with CF from North‐West of Iran .…”
Section: Lessons Learnedmentioning
confidence: 88%